SEISMIC PERFORMANCE ANALYSIS OF 10 STORIES REINFORCED CONCRETE BUILDING USING SPECTRUM RESPONSE AND TIME HISTORY METHODS - Andina Prima Putri; M Ricky Reinaldy Afdar Fadilah; Christianto Credidi Septino Khala (Jurnal Infrastruktur, 2021)
Indonesia is one of the countries located in the most active technonic plate area on earth. These conditions make Indonesia prone to earthquakes. So that the consideration of the load due to earthquakes in structural planning is very important to minimize the impact. Therefore, analysis of the performance of the 10-story reinforced concrete building structure using the response spectrum method and time history aims to determine the basic values of shear, displacement, deviation, and structure performance based on ATC-40. The structural design uses the example of a 10-story reinforced concrete building located in Aceh. The loads refers to SNI 1726:2019 and SNI 1727:2020. The maximum base shear value obtained is 116357.777 kN. The maximum displacement value obtained is 363.841 mm. The drift value does not meet the requirements according to SNI 1726:2019 Article 7.12.1. The structural performance is IO (Immediate Occupancy). Because the drift value does not meet the requirements, a structure evaluation was carried out using the base isolator HDRB HH075X4S. The analysis results show that the base isolator can reduce the base shear value of the structure by up to 73%. The value of displacement value after structural evaluation is 877.394 mm with most of the deformation occurring in the isolation plane so that the structure deforms less and can reduce the drift between floors. The drift value after the evaluation of the structure has met the requirements so that the structure is safer. Structure performance after the same performance evaluation, namely IO (Immediate Occupancy).